Constructing a Risk Management Framework to Protect the Organization - Blair, Garry; Woodcock, Helen; Pagano, Rosane; Endlar, Lewis (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.010 Risk management is a critical activity for every organisation. It is important to consider risk in all operations and balancing risk with reward is an essential component of strategy for most companies, in the context of their environment and the current volatile conditions. This paper discusses the formulation of a risk management framework in order to address this important area, in a comprehensive, structured, planned method. A process for the construction of such a framework is proposed, based on practice. The requirement to scan the organisation’s horizon, discerning the ‘Risk Universe’, possibly using external consultants, is noted. A map of risk coverage should be formulated to ensure adequate protection and remove excessive risk provision. Risk champions can be recruited to disseminate good practice, creating a culture of risk awareness. The organisation’s appetite for risk must be ascertained and a positive contribution made, in respect of environmental issues. A review of the literature was performed and the key themes extracted. A semi-structured interview with a director of an international company was enacted. The main themes were selected, via an inductive approach. The research results were analysed and then utilised to form a proposed procedure for constructing a risk management framework.